Digital imitator of acoustic noises - Моржов, В. І.; Єрмачков, Ю. О. (Problems of Informatization and Control, 2009)
The questions are examined about construction of universal digital imitator of acoustic noises as component part of flight simulator. Design principle of imitator is based on the digital synthesis of signals in a sound frequency range, corresponding to frequency properties of acoustic vibrations that accompany the physical process of aircraft motion and functioning of its onboard systems. Development of imitator is meant as development of software complex by which the synthesis of vibrations is carried out in the necessary frequency band